Roles of Reexamination of Core Beliefs and Rumination in Posttraumatic Growth Among Parents of Children With Cancer: Comparisons With Parents of Children With Chronic Disease. Issue 1 (January 2021) - Irie, Wataru; Shiwaku, Hitoshi; Taku, Kanako; Suzuki, Yuko; Inoue, Yukiko
Abstract : Background: Studies have indicated that the impact of a traumatic experience can be negative and can provide the opportunity to experience psychological growth, known as posttraumatic growth (PTG). Objective: To evaluate the role of cognitive processing in PTG among parents of childhood cancer survivors (CCSs) based on the PTG theoretical model. We compared the model between parents of SCC and parents of children with chronic disease (CCDs) to determine how the role of cognitive processing in PTG is different depending on the children's illness. Methods: Final sample consisted of 78 parents of CCSs and 44 parents of CCDs. The survey included standardized measurements assessing reexamination of core beliefs, intrusive and deliberate rumination, posttraumatic stress symptoms, and PTG. The hypothetical relationships among the variables were tested by covariance structure analysis. Results: Posttraumatic growth among parents of CCSs had significantly strong association with reexamination of core beliefs, but not with deliberate rumination. Reexamination of core beliefs was significantly more likely to foster PTG among parents of CCSs, whereas deliberate rumination was significantly more likely to be associated with PTG among parents of CCDs. Conclusions: For parents of CCSs, reexamination of core beliefs had a greater impact on PTG than deliberate rumination. Our results suggest that support should focus on the process of reexamining core beliefs in facilitating PTG among parents of CCSs. Implications for Practice: Nurses should provide parents of CCSs with reassurance regarding their experiences of the reexamination of core beliefs, which will likely lead to PTG.